An Analysis on the Factors for Cervical Insufficiency Causing Adverse Emotions Among Pregnant Women at Different Gestation Phases - Wu, Qichang; Chen, Jiebing; Zou, Qiaojian; Zeng, Xun; Yang, Yan; Zhou, Yijia; He, Guimei; Luo, Chunqi; Wu, Fengchun (Frontiers in Psychiatry, 2022)
Background: To analyze the anxiety, depression, and related factors among pregnant women with cervical insufficiency, so as to provide a reference for clinical psychological intervention as an adjuvant therapy. Methods: A total of 101 cases with cervical insufficiency were included in the observation group by a convenience sampling method, and 114 normal healthy women of childbearing age were selected as the control group. The subjects were investigated and observed for anxiety and depression by SAS /SDS, so as to analyze the emotional state and influencing factors of the patients with cervical insufficiency. The SPSS20.0 software was used for relevant statistical analysis. If p < 0.05, there was statistical significance for relevant difference. Results: There was statistical significance for the differences in anxiety and depression at different gestation phases in the pregnant women of observation group, but during pregnancy, there was no significant improvement in anxiety with time, while the depression was improved with time. The history of abnormal pregnancy was the main influencing factor for anxiety and depression in the early and middle gestation phases, and cervical insufficiency was the factor influencing the anxiety in early gestation and both anxiety and depression in the late gestation phase. Conclusion: Cervical inadequacy may affect the emotions of pregnant women, and poor psychological states may threaten the maternal and infant health. There shall be appropriate psychological interventions for promoting the maternal and infant health.